2002
DOI: 10.1088/0953-2048/15/8/314
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and superconducting properties of sintered DyBaCuO ceramics doped by Ca

Abstract: The effect of Ca-doping on the microstructure and superconducting properties of sintered stoichiometric Dy1−xCaxBa2Cu3O7−δ (S samples) and Cu-deficient Dy1−xCaxBa2Cu2.8O7−δ (D samples) (x ≤ 0.3) ceramics was studied. The systematic characterization of the fine microstructure was done via conventional and high-resolution observation in TEM as well as fine local energy dispersive x-ray (EDX) analysis in TEM. The distributions of the different types of grain boundaries (clean or coated with a thin or thick film) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…The observed narrowing of intergranular transition could be a result of improvement of intergrain connections and intergranular resistance reduction [23]. All this is in consent with Ca segregation in GB regions, reported by different authors [8,24] Second, the intergranular transition shift, with increasing the frequency, is smaller in Ca substituted sample than in non substituted one. Higher level of overdoping leads to a higher intergranular current, supporting intergranular flux pinning in Ca substituted sample.…”
Section: B Intergranular Flux Pinningsupporting
confidence: 75%
See 1 more Smart Citation
“…The observed narrowing of intergranular transition could be a result of improvement of intergrain connections and intergranular resistance reduction [23]. All this is in consent with Ca segregation in GB regions, reported by different authors [8,24] Second, the intergranular transition shift, with increasing the frequency, is smaller in Ca substituted sample than in non substituted one. Higher level of overdoping leads to a higher intergranular current, supporting intergranular flux pinning in Ca substituted sample.…”
Section: B Intergranular Flux Pinningsupporting
confidence: 75%
“…Using this analogy we can suppose that normal carriers and/or small regions of normal 10 state are present at grain boundaries of overdoped samples. It is known that Ca segregates at the grain boundary regions in substituted Y123 phase [8,24,33].…”
Section: Temperature Dependence Of Critical Current Densitymentioning
confidence: 99%
“…However, the incorporation of Ca on Dy sites in grains led to a substantial decrease in T c of the sample. In the case of predominant Ca substitution for Ba, the intergranular critical current was not improved, but the decrease in T c was much less than for the substitution of Dy [12]. Substitution of Y by Ca in YBa 2−y Ca y Cu 3 O 7−δ was also studied in [13,14] where it was found that, even for a high level of doping (y = 1), T c decreased by about 10 • only.…”
Section: Introductionmentioning
confidence: 99%
“…In [12] we studied the influence of Ca doping on superconducting properties and, first of all, on J c for bulk DyBCO ceramics in which Ca was added as substituent for Dy in amounts equal to Dy deficiency (Dy 1−z Ca z Ba 2 Cu 3 O 7−δ , 0 z 0.3). Using energy dispersive x-ray (EDX) analysis in transmission electron microscopy, it was found that for a large concentration of Ca (z = 0.2-0.3) Ca replaced not only Dy, but also Ba partly.…”
Section: Introductionmentioning
confidence: 99%
“…The substituted atoms produced nanoregions in the material with suppressed T c, and may serve as effective intragranular pinning centers [16,17]. In particular, it has been shown that a small quantity of Ca (2-4%) increases the pinning in Y 1-x Ca x Ba 2 Cu 3 O 7-samples [17][18][19]. The accompanying effect of oxygen vacancy creation, especially in CuO 2 planes should be also important for pinning.…”
Section: Introductionmentioning
confidence: 99%